Medale Stefana Batorego. Uwagi ikonograficzne - Rokita, Jan Gustaw (Studia Europaea Gnesnensia, 2024)
The author of this paper discusses twenty-six works of art, including medals, coins, portrait engravings, emblems as well as specimens of woodcarving and sculpture. Apart from a detailed analysis of the medallic legacy of Stefan Batory, the aim of this study is to find and describe works of art that a medallic artist might have been exposed to when commissioned by the king or his immediate circle to fashion a medal. Having identified direct sources of inspiration for seventeenth-century artists, it has been possible to offer a better explanation of how Stefan Batory promoted his own indisputable political or military achievements.